2018
DOI: 10.1002/bab.1696
|View full text |Cite
|
Sign up to set email alerts
|

Agrowastes utilization by Raoultella ornithinolytica for optimal extracellular peroxidase activity

Abstract: The industrial applications and prospects of microbial peroxidase are on the upwards trend, thus necessitating the search for sources with high turnaround time. Actinobacterial species have been a major source of peroxidase for the obvious reasons of having robust metabolite expression capabilities. However, other bacteria species have been underexplored for peroxidase production, hence the motivation for the investigation into the peroxidase production potential of Raoultella ornithinolytica OKOH-1 (KX640917)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 42 publications
4
14
2
Order By: Relevance
“…However, Musengi et al [12] observed optimum peroxidase production by Streptomyces sp. BSII#1 at pH 8 while we recorded pH 5 as the optimal pH for peroxidase production by Raoultella ornithinolytica OKOH-1 in a recent study [25]. It is worthy of note that the characteristic production of peroxidase by the test bacteria at a neutral pH augurs well for biotechnological applications as the large volume of acid and base required for pH adjustment would be saved [37], consequently, reducing the cost of peroxidase production.…”
Section: Determination Of Process Parameters For Optimal Exoperoxidasmentioning
confidence: 81%
See 4 more Smart Citations
“…However, Musengi et al [12] observed optimum peroxidase production by Streptomyces sp. BSII#1 at pH 8 while we recorded pH 5 as the optimal pH for peroxidase production by Raoultella ornithinolytica OKOH-1 in a recent study [25]. It is worthy of note that the characteristic production of peroxidase by the test bacteria at a neutral pH augurs well for biotechnological applications as the large volume of acid and base required for pH adjustment would be saved [37], consequently, reducing the cost of peroxidase production.…”
Section: Determination Of Process Parameters For Optimal Exoperoxidasmentioning
confidence: 81%
“…It is worthy of note that the characteristic production of peroxidase by the test bacteria at a neutral pH augurs well for biotechnological applications as the large volume of acid and base required for pH adjustment would be saved [37], consequently, reducing the cost of peroxidase production. recent study [25]. It is worthy of note that the characteristic production of peroxidase by the test bacteria at a neutral pH augurs well for biotechnological applications as the large volume of acid and base required for pH adjustment would be saved [37], consequently, reducing the cost of peroxidase production.…”
Section: Determination Of Process Parameters For Optimal Exoperoxidasmentioning
confidence: 97%
See 3 more Smart Citations